Juridical Review of The Implementation of Marine Cargo Insurance On The Sea Freight Agreement at PT. Sinar Mas Insurance - Kusumawati, Elly; Lestari, Elise Dwi; Prawoto, Agus (Green Publisher Indonesia, 2022)
The Indonesian nation is located along equator, a a very strategic potential that crosses between two ocean big, that is Ocean Indian and Ocean Pacific, and between two continent that is Asia and Australia continents. Beside that the Indonesian people have riches diverse nature variety, both on land as well as at sea. Study this aim for get description how Overview Juridical Implementation of Marine Cargo Insurance in the Agreement Freight Sea at PT. Insurance Sinar Mas for interpreted to in a the description presented in form of words. Study this aim for get description how Overview Juridical Implementation of Marine Cargo Insurance in the Agreement Freight Sea at PT. Insurance Sinar Mas for interpreted to in a the description presented in form of words. because of that, research this use approach qualitative descriptive. Condition coverage in Marine Cargo Insurance guaranteed by PT. Insurance Sinar Mas serves 3 (three) conditions coverage. Election condition by the insured influence quantity premium must paid as well as breadth guarantee the danger posed by the insurer. So that the consequences is condition of the policy purchased in accordance the dangers that can guaranteed that 's what can submitted accompanied completeness document claim.